Believes, attituds and feelings in nursing students and proffesors facing the covid-19 pandemic - Hernández Vicente, Irma Alejandra; Hernández-Ramírez, Magdalena; Lumbreras-Delgado, Irma; Juárez-Flores, Clara Arlina; Báez-Alvarado, María del Rocío; Banderas-Tarabay, José Antonio Banderas-Tarabay (Horizonte Sanitario, 2022)
Objective: To identify what believes, attitudes and feelings are in nursing students and professors in the Health Sciences Faculty at the Universidad Autonoma de Tlaxcala, facing the Covid-19 pandemic.Material and Methods: A descriptive and transversal study using a convenient sample population of students and professors in nursing, to whom a questionnaire was sent via internet, previously validated to determine beliefs, attitudes and feelings facing an epidemiologic alert. A descriptive analysis was done in the statistic program SPSS v27.Results: The most common feeling found are: being afraid of infecting a family member or a close friend, the death of a family member or a close friend, not getting appropriate orientation or training by the institution where they work or study to prevent an infection; Though they are conscious of the risk working with infected patients, and also by the responsibilities when attending classes or teaching in a classroom. The feeling for being discriminated by the people is low, thus because they are in risk of infecting other persons.Conclusions: Being afraid of being contagious or widespread the infection within the family members, suffering feelings of guilt over infecting students and professors. Both of them, are conscious of the risk to be infected, and all them claim the institution for protection and orientation programs to avoid the infection by Covid-19.Key words: Culture; Attitudes; Emotions; Coronavirus infections.